2018
DOI: 10.1021/acs.langmuir.8b01168
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell–Corona Micelles from a Polyether-Based Triblock Terpolymer: Investigation of the pH-Dependent Micellar Structure

Abstract: Core-shell-corona micelles featuring a pH-responsive shell have been characterized in dilute aqueous solution at different pH values (4-8) by using dynamic light scattering (DLS), field-flow fractionation coupled with multiangle light scattering detector (FFF-MALS), steady-state fluorescence, small-angle X-ray scattering (SAXS), and cryogenic transmission electron microscopy (cryo-TEM). The micelles are formed by self-assembly of a polyether-based triblock terpolymer consisting of a hydrophobic poly( tert-buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For example, batch DLS was able to detect the aggregates present in a formulation of poly(lactic-coglycolic acid) (PLGA) nanoparticles, while said aggregates disappeared when the formulation was analyzed by SdFFF due to the spatial separation among solutes [76]. In a similar fashion, excessively high flows could induce particle disruption due to shear forces [77].…”
Section: Particle Sizementioning
confidence: 99%
“…For example, batch DLS was able to detect the aggregates present in a formulation of poly(lactic-coglycolic acid) (PLGA) nanoparticles, while said aggregates disappeared when the formulation was analyzed by SdFFF due to the spatial separation among solutes [76]. In a similar fashion, excessively high flows could induce particle disruption due to shear forces [77].…”
Section: Particle Sizementioning
confidence: 99%
“…Polyethers are widely used in drug and vaccine delivery and as polymer electrolytes and non-ionic surfactants. [1][2][3][4][5][6][7][8][9][10] Poloxamer materials are a particular subset of non-ionic, ABA block polyethers containing a central hydrophobic PPO block flanked by two outer hydrophilic poly(ethylene oxide) (PEO) blocks (i.e., PEO-b-PPO-b-PEO). Other poloxamer-like materials with diverse architectures have been developed with the same design strategy of a hydrophobic midblock with PEO outer blocks on either side.…”
Section: Introductionmentioning
confidence: 99%
“…7,14 Unfortunately, many studies utilizing BAB triblock polymers focus on polymers with relatively short end blocks compared to their poloxamer counterparts. 10,[15][16][17][18][19][20][21] Jung et al showed that simply tuning the hydrophobicity of BAB triblocks by altering the hydrophobic block composition could significantly alter hydrogel relaxation dynamics; however, none of their hydrophilic end blocks exceeded 3.0 kg/mol in total. 16 Even traditional PPO-b-PEO-b-PPO RP materials such as the commercially available 25R4 and 31R1 RPs are lower molecular weight (ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations